Pengaruh Pemanfaatan Mobile Banking, Dana Pihak Ketiga, Jumlah Kantor, dan Jumlah Pembiayaan Terhadap Kinerja Keuangan Bank Syariah di Indonesia Periode 2020-2024 - Ratna Himatul Aina; Lintang Kurniawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Financial performance is an important measure in assessing the effectiveness and efficiency of a company. This study aims to examine the effect of mobile banking utilization, third-party funds, number of offices, and number of financing on financial performance. The research population includes Sharia Commercial Banks registered with OJK and Bank Indonesia during the period 2020–2024. The sample selection was conducted using purposive sampling, resulting in 11 Islamic Commercial Banks that met the research criteria with a total of 46 observations from a total population of 14 companies. Financial performance was proxied by Return on Assets (ROA). This study used a quantitative approach with secondary data in the form of annual financial reports, and was analyzed using multiple linear regression through the SPSS version 25 program. The results showed that third-party funds and the amount of financing had an effect on financial performance, while the use of mobile banking and the number of offices had no effect on financial performance.